SIMULATION OF THE APPLICATION OF RESISTANCE EXERCISE AND WARM WATER SOAKING COMBINATION IN MAINTAINING THE SENSITIVITY OF THE FEET OF DIABETES MELLITUS PATIENTS - ARUM DWI NINGSIH (EZRA SCIENCE BULLETIN, 2025)
Diabetes Mellitus (DM) is a condition where there is a disruption in the body's metabolic processes. One of the most common long-term complications of DM is peripheral neuropathy, especially in the lower extremities, which causes decreased sensitivity in the feet. The purpose of community service activities is to increase public knowledge about Diabetic Neuropathy and skills regarding procedures for performing resistance exercises and warm water immersion. The methods in this activity are socialization, education, simulation, mentoring, evaluation, and program sustainability. The results of community service activities include evaluating the level of knowledge with the Wilcoxon Rank Test statistical test, which shows that the p value = 0.000 (p <0.005). Therefore, it can be concluded that education and simulation can increase public knowledge regarding Diabetic Neuropathy and skills in performing Resistance exercises and warm water immersion.